Identification of factors associated with satisfaction of farmers-group members in Kwara State Nigeria - Sola Emmanuel Komolafe; Adeseye Olusikemi Awoyemi; Saheed Olayinka Jimba; Gbolagade Benjamin Adesiji (Serambi Journal of Agricultural Technology, 2020)
The satisfaction of members is fundamental to group cohesion and eventual maximization of the potential of farmer groups as catalysts for agricultural and rural development in Nigeria. The study examined the factors associated with membership satisfaction in Irepodun Local Government Area of Kwara State, Nigeria. A two-stage random sampling procedure was used to select 120 respondents on which a questionnaire was administered. Descriptive statistics involving frequency counts, percentages, means and the Likert scale were used to present the results of the study. Pearson’s Product Momment Correlation and Chi-square analyses were used to test the hypotheses of the study. The result revealed that all the members were male (100%), married (97.5%) and had no formal education (68.3%). The groups were well organized as revealed by their regular meetings, democratically elected leadership and payment of dues. However joint ownership of assets was poor among the groups. Majority of the members benefitted in farm credit (100%), social gains (92.5%) and input distribution (73.3%). A moderate level of satisfaction (mean=3.01) was observed among members mostly in usage of monthly due (mean=4.62), timing of farmer's group (mean=4.06) and performance of your group officials (4.00). The factors associated with membership satisfaction were farm size and household size while derivation of benefits such as access to credit, input, extension training and social gains also positively influenced membership satisfaction. The study concluded that membership satisfaction was moderate and influenced by the identified factors. It therefore recommended farmers group should consider farm size of each members while distributing benefits like farm credit and inputs.